Praktiken medialer Transformationen : Übersetzungen in und aus dem digitalen Raum - Schmid, Johannes C. P.; Veits, Andreas; Vorrath, Wiebke (Digitale Gesellschaft, 2018)
At the border between that which is analogous and that which is digital: Transformations into and from digital spaces are made tangible and placed (media- ) culturally by humanistic approaches.